Polystichum alluvium (subg. Haplopolystichum; Dryopteridaceae), a new cave species from Guizhou, China, with reference to new distribution records of P. leveillei - Lu, Ngan Thi; Duan, Yi-Fan; Zhang, Li-Bing (Phytotaxa, 2017)
A new fern species, Polystichum alluvium, a member of P. subg. Haplopolystichum (Dryopteridaceae), is described from Guizhou Province in Southwest China. Polystichum alluvium is similar to P. lanceolatum in having small habit and subcoriaceous pinnae, but the former has oblanceolate laminae with basal pinnae strongly contracted toward lamina base, deltoid-ovate and sessile pinnae, and very short spinules on acroscopic pinna margins or no spinules, while the latter has lanceolate laminae with basal pinnae not contracted toward lamina base, oblong and petiolate pinnae, and long spinules on acroscopic pinna margins. Polystichum alluvium was found from the alluvial bottom of a karst cave at an elevation of 1410 m with humid and shady conditions and is currently known from one population with ca. 50 plants in western Guizhou. It is classified as Critically Endangered (CR) following IUCN Red List criteria. We also expanded the distribution of P. leveillei to southern-central Guizhou based on our new collections.